Social Innovations in Geo-Ict Education at Tanzanian Universities for Improved Employability (GEOICT4E) - Käyhkö Niina; Mbise Mercy; Ngereja Zakaria; Makame Makame O.; Mauya Ernest; Matto George; Timonen-Kallio Eeva; Rancken Romi (Germany, 2022)
Geospatial and ICT technologies are making an impact leap due to globally accessible open data solutions addressing environmental and social challenges, such as rapid urbanization, degradation of marine and land environments, and humanitarian crises. We are witnessing a rapid growth of innovations built on data and tools tackling local societal problems. At best, these can provide better opportunities for sustainable solutions and development. The need for geospatial expertise is growing globally, and the required skills and capabilities of experts are changing. Universities need to think that although the future jobs rely on experts’ geospatial data and technology skills, graduates need to have a strong conceptual and practical understanding of societal problems and capacity to co-develop solutions, which generate wellbeing and inclusive development. New generation university graduates need to master the interface between technologies’ potential and societies’ emerging needs, working in a multi-stakeholder environment and creating innovative and impactful solutions. In this paper, we present a model of institutional cooperation between five Tanzanian and three Finnish universities, aiming to tackle this transformative education challenge in Tanzania. GeoICT4e aims to develop innovative and scalable geospatial and ICT e-learning services for Tanzanian universities. Via this transformation, universities are aiming to enhance the future employment potential of the graduates with digital multi-competence skills. We present the overall methodology and key activities of the project cooperation, and discuss the opportunities and challenges related to this transformation, and use of open data and FOSS solutions particularly from the institutional and societal perspectives.
The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, Volume XLVI-4/W2-2021: FOSS4G 2021 – Academic Track, 27 September–2 October 2021, Buenos Aires, Argentina